2002
DOI: 10.1136/jramc-148-03-03
|View full text |Cite
|
Sign up to set email alerts
|

Sports And Training Injuries In British Soldiers: The Colchester Garrison Sports Injury And Rehabilitation Centre

Abstract: Objectives: To record and analyse the injuries and conditions requiring referral to the Colchester Garrison Sports Injury and Rehabilitation Centre over a three year period, with special reference to type and site of injury, aetiology, and outcome.Methods: An ongoing prospective study in which data on the diagnosis, cause of injury, and treatment of all patients referred to the Centre was coded and stored on a database. A total of seventeen variables were recorded.Subjects: All patients were trained, serving s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
20
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…[1][2][3][12][13][14] According to several studies, 1-3 the majority of ankle sprains documented within military personnel result from participation in organized and recreational sports, exercise, and physical training. Ankle sprains are not an isolated problem affecting US service members, as authors have documented a high rate of sportrelated, exercise-related, and physical training-related ankle sprains in British Army 3,13 and New Zealand Defense Force 2 populations. Lauder et al 1 found that ankle injuries, and ankle sprains specifically, were second only to knee injuries among hospital admissions for sportrelated and physical training-related injuries between 1989 and 1994 in the US Army.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[1][2][3][12][13][14] According to several studies, 1-3 the majority of ankle sprains documented within military personnel result from participation in organized and recreational sports, exercise, and physical training. Ankle sprains are not an isolated problem affecting US service members, as authors have documented a high rate of sportrelated, exercise-related, and physical training-related ankle sprains in British Army 3,13 and New Zealand Defense Force 2 populations. Lauder et al 1 found that ankle injuries, and ankle sprains specifically, were second only to knee injuries among hospital admissions for sportrelated and physical training-related injuries between 1989 and 1994 in the US Army.…”
Section: Discussionmentioning
confidence: 99%
“…1 Among service members, ankle sprains frequently result in time loss and persistent disability 6 and are second only to low back pain in relation to the overall percentage of rehabilitation workload. 3 Strowbridge and Burgess 3 reported that ankle sprain injuries among British Army personnel required an average of 40 days of rehabilitation. Gerber et al 6 noted persistent disability associated with ankle sprains during a prospective investigation within a cohort of cadets at the US Military Academy at West Point.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Their results included acute and chronic injuries but showed training injuries accounted for 35.2% of referrals and sporting injuries for 28.5% of referrals; therefore, training injuries were a greater problem than sporting injuries. 9 Efforts have been made (successfully) to reduce these sporting injuries through education and simple means. 10,11 The ASPT has long had a policy of recruiting those with high fitness levels as low levels of physical fitness have been linked with increased injury rates.…”
Section: Discussionmentioning
confidence: 99%